Mucormycosis as a complication of COVID-19 coronavirus infection: eye symptoms - A. E. Babushkin; L. I. Gilemzianova; I. P. Ponomarev (Российский офтальмологический журнал, 2024)
COVID-19 causes an immunosuppressive condition and increases the risk of secondary infections, including fungal diseases such as mucormycosis (MM), so doctors should be aware of the possibility of MM development in COVID-19 patients. Since no specific complaints or clinical symptoms exist and the disease is rare, especially in developed countries with a moderate climate, it is often impossible to diagnose MM at the initial examination. Therefore, the detection of the pathogen (mycelium zygomycetes) plays a key role in the diagnosis. Over 70 % of MM patients experience eye damages. According to the literature, the most common manifestations thereof are blepharoptosis, ophthalmoplegia, exophthalmos, injection and conjunctival chemosis. Quite often, the patients have eye pains, orbital cellulitis or phlegmon of the orbit, accompanied by a decrease in vision. For the effective treatment of this severe infectious COVID-19 complication, which takes the form of deep and aggressive mycosis, an interdisciplinary approach is necessary. The complex treatment should make use of antimycotic agents and symptomatic therapy, and, essentially, surgical rehabilitation of infection foci by removing the affected necrotic tissues. The prognosis is always very serious.